(untitled) (UNED Research Journal, 2019)
the size (N) of the crocodilian populations can rarely be determined accurately. Objective: to compare methods, the abundance of Caiman crocodilus was estimated for a single population in Costa Rica with spatially replicated counts, with the N-mixture Model and the Messel Method. Methods: I counted caimans at night along 21km of the river Frío (Betel-Boga Sabogal). I divided the stretch into 32 segments (500m) spaced 200m from each other. Results: the N-Mixture model produced an estimate of 2 162 individuals and the Messel 373. Conclusion: spatially replicated counts, analyzed with the N-Mixture model, seem to provide more reliable data.